Análise de vídeos exibidos no Programa CQC - Conceição, Tatiane Silva da (2012)
This paper aims to make an exploratory study with the analysis and transcription of videos CQC program (at any cost), Rede Bandeirantes Television. From this analysis, it was concluded that the program presents the characters so stereotyped, partial (in some cases the approach is neutral on other, positive, others negative), superficial and so contribute to the "spectacle of Politics "and as another representative of the "infotainment". In some cases appears to critique the political practices, such as the privilege, but the complaint is often treated with derision by the politicians themselves and fall into the void, being seen as "a joke anymore." However, even then, it is good to have freedom a program to address the political form of humor because it approximates the average citizen and the freedom of expression also denotes something fundamental to the democratic rule of law